Growth mindset results in reduced trait attribution and more rehabilitative judicial decisions in cases of juvenile delinquency - Li, Ning (Legal and criminological psychology, 2025)
Background With the framework of the mindset theory and previous findings in adult criminal justice, this research explores how growth mindset—the belief that personal traits are malleable—affects judicial decision-making in juvenile justice. Aims We aim to examine the hypotheses that laypeople with growth mindset tend to endorse more rehabilitative motivations and decisions (H1) through reduced trait attribution (H2). Materials and Methods We measured (Study 1) and experimentally manipulated (Study 2) growth mindset to test H1 and H2 with samples of laypeople. Studies 3A and 3B used data from professional judges and prosecutors in China to test the generalizability. Study 4 replicated the measures from Studies 3A and 3B with a laypeople sample to facilitate cross-sample comparisons. Results Studies 1 and 2 provide correlational and causal evidence, respectively, supporting both H1 and H2. However, Studies 3A and 3B did not yield significant results among judicial experts. Study 4 re-confirmed the hypotheses in lay participants. Judges with juvenile case experience showed a weaker association between growth mindset and probation decisions compared to their less specialized peers and laypeople. A similar pattern emerged among prosecutors, though the findings were not statistically significant. Discussion The current research highlights growth mindset as a key belief driving public support for rehabilitative approaches in juvenile justice. Specialized judicial expertise appears to mitigate this association, suggesting a nuanced interaction between lay beliefs and judicial specialization. Conclusion Growth mindset of laypeople results in their reduced trait attribution and more rehabilitative judicial decisions in cases of juvenile delinquency.